2019
DOI: 10.1007/s12237-019-00636-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Exchange Flow During Spring Tide and Its Cause in the Sumjin River Estuary, Korea

Abstract: Knowledge of exchange flow and its variations is important, because it determines the distribution of salt, nutrient, pollutant, and suspended sediment in estuaries. Although exchange flow has been studied extensively, their variations over the spring-neap tidal cycle remain unclear. Many studies have indicated that the exchange flow is weaker during spring tides than neap tides, but others have reported that it might be stronger during spring tides. Therefore, we investigated the spring-neap variation of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Even when the salinity gradient was estimated by averaging the salinity at various water depths, there was almost no change. In the analytical model using the balance equation of pressure gradient and friction (Cho et al, 2020), the observed exchange flow was well realized when the horizontal length scale was set at a 1 km interval when calculating the salinity gradient. Therefore, we used the salinity from the surface layer to the bottom and set the horizontal length to 1 km to calculate the salinity gradient.…”
Section: Comparison Of Salinity and Current Between Observations And ...mentioning
confidence: 94%
See 4 more Smart Citations
“…Even when the salinity gradient was estimated by averaging the salinity at various water depths, there was almost no change. In the analytical model using the balance equation of pressure gradient and friction (Cho et al, 2020), the observed exchange flow was well realized when the horizontal length scale was set at a 1 km interval when calculating the salinity gradient. Therefore, we used the salinity from the surface layer to the bottom and set the horizontal length to 1 km to calculate the salinity gradient.…”
Section: Comparison Of Salinity and Current Between Observations And ...mentioning
confidence: 94%
“…In a previous study of the Sumjin River estuary, the salinity gradient was the main determinant in the fortnightly variation of exchange flow in the lower estuary (Cho et al, 2020). To determine what mechanism caused the variation in the intensity of the exchange flow in the entire estuary, we compared the salinity gradient and vertical mixing effect, which are the main factors that determine the vertical shear of the exchange flow.…”
Section: Fortnightly Variation In Exchange Flow and Its Causementioning
confidence: 99%
See 3 more Smart Citations